Taguchi optimization design of diameter-controlled synthesis of multi walled carbon nanotubes for the adsorption of Pb(II) and Ni(II) from chemical industry wastewater - Egbosiuba, Titus Chinedu (2021)
Herein, Taguchi L9 orthogonal array was used for the first time to optimize synthesis of diameter-controlled multi walled carbon nanotubes (MWCNTs). The nanoadsorbents, MWCNTs5-15 nm and MWCNTs16-25 nm were applied for Pb(II) and Ni(II) ion removal from paint, battery and electroplating wastewater. The results indicated successful synthesis of MWCNTs with diameter distribution ranges of 5-15 nm and 16-25 nm. The synthetized smaller diameter MWCNTs5-15 nm revealed higher Brunauer-Emett-Teller (BET) surface area of 1306 ± 5 m2/g compared to larger diameter MWCNTs16-25 nmwith the surface area of 1245 ± 4 m2/g. They demonstrated excellent adsorption of Pb(II) and Ni(II) ions within the permissible concentration proposed by WHO at pH, contact time, adsorbent dosage and temperature of 5, 60 min, 30 mg/L and 50 °C, respectively. Particularly, MWCNTs5-15 nm possessed high adsorption capacity of 215.38 ± 0.03 mg/g for Pb(II) and 230.78 ± 0.01 mg/g for Ni(II). Again, the maximum adsorption capacity of 201.35 ± 0.02 and 206.40 ± 0.02 mg/g was achieved for Pb(II) and Ni(II) using MWCNTs16-25 nm. All in all, the adsorption capacity of the nanoadsorbents at the investigated diameter range showed higher efficiency compared to other materials for heavy metals elimination from chemical industrial wastewater.